2018
DOI: 10.1007/s00264-018-3953-4
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell therapy in bilateral osteonecrosis: computer-assisted surgery versus conventional fluoroscopic technique on the contralateral side

Abstract: The findings of this study suggest that computer navigation may be safely used in a basic procedure for injection of stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Several previous studies [12,13,21,35] focused on cell therapies have found that there was a clinical improvement of symptoms on patients with ONFH including pain and function scores. However, the efficacy of stem cells in the long term is not clear and remains controversial especially on the progression events [9,11,12,36,37].…”
Section: Discussionmentioning
confidence: 98%
“…Several previous studies [12,13,21,35] focused on cell therapies have found that there was a clinical improvement of symptoms on patients with ONFH including pain and function scores. However, the efficacy of stem cells in the long term is not clear and remains controversial especially on the progression events [9,11,12,36,37].…”
Section: Discussionmentioning
confidence: 98%
“…The authors [37,[40][41][42][43][44] of this issue critically address specific problems-namely cell quality and competence, and microenvironmental changes occurring at the bone osteonecrosis level. BMSC-which are supposed to be Bfunctionally competent^-are often being collected from the BM of patients with bone disease and concomitant risk factors for bone marrow disease (corticosteroids, alcohol abuse…).…”
Section: Cell Therapy and Osteonecrosismentioning
confidence: 99%
“… 9 , 11 Previous studies have demonstrated the accuracy of cup placement in DDH patients with CT. 12 , 13 Moreover, a navigation system has been used not only for THA but also for hip resurfacing arthroplasty, periacetabular osteotomy, and stem cell therapy in osteonecrosis of the hip. 14 - 17 …”
Section: Introductionmentioning
confidence: 99%